1985
DOI: 10.1139/v85-418
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of interaction of aromatic solutes with organic solvents

Abstract: Heats of solution of several aromatic solutes (benzene, toluene, mesitylene, nitrobenzene, α,α,α-trifluorotoluene, anisole) and model compounds (n-butyl methyl ether, cyclohexane) in 17 organic solvents (n-heptane, cyclohexane, carbon tetrachloride, 1,2-dichloroethane, α,α,α-trifluorotoluene, triethylamine, butyl ether, ethyl acetate, dimethylformamide, dimethyl sulfoxide, benzene, toluene, mesitylene, t-butyl alcohol, 1-octanol, methanol, 2,2,2-trifluoroethanol) have been combined with solute heats of vaporiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The application was tested on a set of 270 zeotropic and azeotropic systems of homogeneous binary solutions and 30 non‐homogeneous systems. In addition to the VLE data, values of the excess properties ( v E and h E ) have been used and, also, LLE data of the system studied, extracted from the literature,…”
Section: Results Of the Testmentioning
confidence: 99%
“…The application was tested on a set of 270 zeotropic and azeotropic systems of homogeneous binary solutions and 30 non‐homogeneous systems. In addition to the VLE data, values of the excess properties ( v E and h E ) have been used and, also, LLE data of the system studied, extracted from the literature,…”
Section: Results Of the Testmentioning
confidence: 99%
“…Additionally, we believe that the aromatic moieties of the molecules composing the DM fraction are also exposed so that they can interact with silanol groups through weak hydrogen bonds. Many authors have reported nonclassic hydrogen bonding between aromatic moieties and silica surfaces. , Figures S-15–S-19 of the Supporting Information show the molecular composition of common classes in W, WD, NE, DM, and T.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have reported nonclassic hydrogen bonding between aromatic moieties and silica surfaces. 66,67…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Many studies have been performed by Fuchs et al , on the determination of enthalpies of interaction of polar and nonpolar solutes with polar or nonpolar solvents, and many organic compounds have been tested. Solomonov et al have developed methods for extracting the enthalpy of specific solute−solvent interaction based on the basic relationship above (eq 11).…”
Section: Resultsmentioning
confidence: 99%
“…There is lacking of data of their enthalpies of sublimation or lattice energies which are to be estimated. The calorimetric procedure described in the literature was followed . The results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%